Why some firms thrive while others fail : governance and management lessons from the crisis - Stanton, Thomas H., 1944- (New York ; Oxford : Oxford University Press, 2012)
Why did some firms weather the financial crisis and others not? This book investigates the inner workings of over a dozen major financial and nonfinancial companies, reveals what went wrong and proposes a remedy.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on July 16, 2012).
Keywords: Corporations -- United States -- Case studies; Industrial management -- United States -- Case studies; Global Financial Crisis, 2008-2009.